Aging Leads to Increased Monocytes and Macrophages With Altered CSF-1 Receptor Expression and Earlier Tumor-Associated Macrophage Expansion in Murine Mesothelioma - Duong, Lelinh; Pixley, Fiona J.; Nelson, Delia J.; Jackaman, Connie (Frontiers in Aging, 2022)
Increased cancer incidence occurs with the emergence of immunosenescence, highlighting the indispensability of the immune system in preventing cancer and its dysregulation with aging. Tumor-associated macrophages (TAMs) are often present in high numbers and are associated with poor clinical outcomes in solid cancers, including mesothelioma. Monocytes and macrophages from the bone marrow and spleen can respond to tumor-derived factors, such as CSF-1, and initiation of the CSF-1R signaling cascade results in their proliferation, differentiation, and migration to the tumor. Age-related changes occur in monocytes and macrophages in terms of numbers and function, which in turn can impact tumor initiation and progression. Whether this is due to changes in CSF-1R expression with aging is currently unknown and was investigated in this study. We examined monocytes and macrophages in the bone marrow and spleen during healthy aging in young (3-4 months) and elderly (20-24 months) female C57BL/6J mice. Additionally, changes to these tissues and in TAMs were examined during AE17 mesothelioma tumor growth. Healthy aging resulted in an expansion of Ly6Chigh monocytes and macrophages in the bone marrow and spleen. CSF-1R expression levels were reduced in elderly splenic macrophages only, suggesting differences in CSF-1R signaling between both cell type and tissue site. In tumor-bearing mice, Ly6Chigh monocytes increased with tumor growth in the spleen in the elderly and increased intracellular CSF-1R expression occurred in bone marrow Ly6Chigh monocytes in elderly mice bearing large tumors. Age-related changes to bone marrow and splenic Ly6Chigh monocytes were reflected in the tumor, where we observed increased Ly6Chigh TAMs earlier and expansion of Ly6Clow TAMs later during AE17 tumor growth in the elderly compared to young mice. F4/80high TAMs increased with tumor growth in both young and elderly mice and were the largest subset of TAMs in the tumor. Together, this suggests there may be a faster transition of Ly6Chigh towards F4/80high TAMs with aging. Amongst TAM subsets, expression of CSF-1R was lowest in F4/80high TAMs, however Ly6Clow TAMs had higher intracellular CSF-1R expression. This suggests downstream CSF-1R signaling may vary between macrophage subsets, which can have implications towards CSF-1R blockade therapies targeting macrophages in cancer.